Prevalence of anaemia among young girls and pregnant women of Birgunj, Nepal - Adak, M; Nazri, S (Journal of Institute of Medicine Nepal, 2007)
Background. The prevalence of anaemia is a major health problem worldwide and is high particularly among young girls and pregnant women. A perusal of the literature on anaemia prevalence in semi urban areas of Nepal is very alarming and its magnitude increases day to day. Methods: All the patients with illness attending at OPD of NMC Hospital were included in the study. Social demographic profile, morbidity data were recorded on a structured questionnaire. Anthropometric measurements and BMI were recorded on the basis of National Health and Nutritional Examination Survey. Hb was estimated by Sahli’s method and pregnancies were verified with urine specimen using on HCG testing kit. Results. In the sample of 552 patients, 54-64.2 % were anaemic .Out of which, 26.9 % of pregnant women were moderately anaemic and 3.1 % subject were severe anaemic. Conclusions. Higher prevalence of anaemia among young in Birgunj was alarming looking due to either lesser consumption of green leafy vegetable or habit of post meal tea/coffee drinking or smaller intake of citrus fruits. These findings suggest that guideline for screening for anaemia may need to further study in relation to the dietary level of iron, iron and ferritin level in blood. Key words: Anaemia, young girls, pregnant women, semi urban areas The full text of this paper is available at Journal of Institute of Medicine website